Hypothesis: Coupling between Resorption and Formation in Cancellous bone Remodeling is a Mechanically Controlled Event - Erben, Reinhold G. (Frontiers in Endocrinology, 2015)
Coupling is the process that links bone resorption to formation in a temporally and spatially coordinated manner within the remodeling cycle. In order to maintain skeletal integrity, it is of crucial importance that the amount of bone resorbed matches the amount of newly formed bone in each remodeling site. Although a number of different explanatory models have been developed, the mechanisms that couple bone resorption and formation in bone remodeling are still a matter of controversy. Here, I propose a model in which coupling is achieved by biomechanical strain sensed by osteocytes within the newly built bone package. In this model, the resorption cavity created by osteoclasts results in mechanical weakening of the structural element, and, thus, in increased strain under constant loading conditions. Subsequent bone formation is initiated by strain-sensitive osteocytes in the underlying bone matrix. After osteoblastic bone formation has started, the newly built osteocyte-osteoblast network detects strain. Once the mechanical strain within the newly built bone structural unit falls below a certain threshold, bone formation stops. In this biomechanical strain-driven model, osteoblasts don’t need to “know” how much bone was previously resorbed in a given site. In addition, this model does not require the transfer of any information from bone-resorbing osteoclasts to bone-forming osteoblasts, because biomechanical strain “guides” osteoblasts through their job of re-filling the resorption cavity.